2008
DOI: 10.1016/j.febslet.2008.10.018
|View full text |Cite
|
Sign up to set email alerts
|

A putative physiological role of hypothalamic CNTF in the control of energy homeostasis

Abstract: Administration of CNTF durably reduces food intake and body weight in obese humans and rodent models. However, the involvement of endogenous CNTF in the central regulation of energy homeostasis needs to be elucidated. Here, we demonstrate that CNTF and its receptor are expressed in the arcuate nucleus, a key hypothalamic region controlling food intake, and that CNTF levels are inversely correlated to body weight in rats fed a high-sucrose diet. Thus endogenous CNTF may act, in some individuals, as a protective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…5A, lane M). The fact that CNTFR␣ was not detected in the membrane fraction, although functional after an intraperitoneal injection of CNTF (34,57), may be due to its labile glycosyl-phosphatidylinositol anchorage to the cell membrane (14). Moreover, JAK2 and Akt were detected in both cytoplasmic and nuclear fractions (Fig.…”
Section: Cntf and Its Receptor Subunits Are Expressed In Anorexigenicmentioning
confidence: 99%
See 3 more Smart Citations
“…5A, lane M). The fact that CNTFR␣ was not detected in the membrane fraction, although functional after an intraperitoneal injection of CNTF (34,57), may be due to its labile glycosyl-phosphatidylinositol anchorage to the cell membrane (14). Moreover, JAK2 and Akt were detected in both cytoplasmic and nuclear fractions (Fig.…”
Section: Cntf and Its Receptor Subunits Are Expressed In Anorexigenicmentioning
confidence: 99%
“…We have demonstrated previously that CNTF was expressed in 90% of astrocytes and 75% of neurons in the rat ARC (57). Because CNTF administration decreases food intake, we addressed the possibility for the cytokine to be produced in anorexigenic neurons.…”
Section: Cntf and Its Receptor Subunits Are Expressed In Anorexigenicmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein encoded by ZFP91 is a potent survival factor for neurons and also acts as a regulator of the noncanonical NF-κβ pathway. In addition, a read-through transcript variant composed of ZFP91 and the downstream ciliary neurotrophic factor (CNTF) gene, an endogenous modulator of energy homeostasis in the arcuate nucleus (35), has been reported. We observed that male offspring of HFD-fed dams, which were born large according to the mean weight of their littermates (above 80th percentile), had higher levels of DNA methylation in the ZFP91 promoter (data not shown).…”
Section: Reviewmentioning
confidence: 99%